Ethics briefing - Michaux, Natalie; Meaburn, Emma; Mussell, Rebecca (Journal of medical ethics, 2024)
The bill was carried through the Sénat, however, with its Law Commission indicating prior to debate that it would not oppose making abortion a constitutional freedom, despite ‘some reservations’ about the text of the bill.3 Some of the issues raised in the Assemblée related to the language used, with some parliamentarians preferring to constitutionalise the ‘droit’ (right) to abortion; in line with language used in previous debates on the subject, rather than the term ‘liberté’ that was settled on.4 Other concerns were raised about the appropriateness of ‘preventative constitutionalisation’,5 the potential impact on a clinician’s ability to exercise conscientious objection6 and fears of creating an imbalance more generally between women’s rights and broader human rights.7 The French minister for justice countered the latter, stating that abortion is different to other freedoms as it gives women the ability to decide their own future.1 He clarified that inscribing abortion as a constitutional freedom did not mean that the right to access was ‘absolute or without limits’.1 In another European move, and in line with other states that have sought to introduce ‘buffer zones’ to reduce the adverse impact of antiabortion activities outside services, Germany is seeking to introduce a law prohibiting the harassment of people entering or leaving abortion clinics. Individuals who break the law will be fined up to €5000.8 German lawmakers have said the law is necessary to stop people using abortion clinics being faced with ‘hatred and agitation’,8 Abortion remains illegal (with exceptions) under the German Criminal Code9 and a number of other practical barriers to accessing abortion remain, such as finding a clinic that will perform one.8 The new law—dubbed the ‘pavement harassment law’10—has come under fire from antiabortion activists, who describe their protests as ‘peaceful’ and claim that the prohibition of them is antidemocratic.8 Public asked to shape future use of NHS ‘federated’ health data In November 2023, National Health Service England (NHSE) procured a federated data platform (FDP). Specific concerns raised include lack of clarity around added value, integrity and transparency of the procurement process and the nature of the supplier’s relationship with and access to patient data.13 Campaigning organisations, including the Doctors’ Association UK, have initiated legal proceedings against the decision to award the FDP contract to Palantir, setting out worries around the potential misuse of data among others.14 The UK Government’s National Data Guardian has urged NHSE to learn from previous high-profile data sharing failures such as care.data,15 stating it is ‘vital…to communicate and engage effectively with the public and professionals to maintain trust in how the NHS handles people’s data’11 and that ‘there must be no surprises for people about how their private information is being used’.16 NHSE has recently announced plans for a series of public engagement activities to ‘actively engage and involve patients and the public in decisions on how data are used with the FDP’.17 These events will continue until March 2025, and are supported by the independent Health Data Patient and Public Engagement and Communications Advisory Panel and the FDP Check and Challenge Group. The report envisages that the NHS would retain a controlling stake of the NHSDT, with additional investments from other companies, to ensure that operations remain aligned with public health objectives rather than the priorities of private capital investors.20 The institute claims that opening up access to NHS record data would allow private actors to leverage the wealth of longitudinal comprehensive health data that they otherwise ‘lack the co-ordination and scope to produce’ to facilitate health research and discovery for the overall benefit of public health.20 The report is careful to state that any implementation of the proposals would need ongoing consideration and debate, especially in relation to responsible and transparent governance, allay any concerns around security and data misuse and to ensure that patient privacy is properly protected.20 Ultimately, the report proposes that the NHSDT could be combined with population-level data resources such as Our Future Health, Genomics England and UK Biobank to train and implement artificial intelligence (AI)-based healthcare, leading to personalised ‘AI doctors’ that complement and assist human clinicians to help meet demand for services and relieve pressure on the NHS.20 Additional recommendations in the report include the establishment of a ‘Laboratory of Biodesign’ that will harness talent and expertise in computation and biology to design and build new biotechnologies, biomolecules and therapeutics, helping position the UK ‘at the frontier of biotech research’; and the creation of a new ‘UK Biosecurity Taskforce’ to learn lessons from the COVID-19 pandemic and develop plans for a biosecure society.20 Ethics statements Patient consent for publication Not applicable.